IDENTIFIKASI MASALAH-MASALAHSISWA LAKI-LAKI DAN SISWA PEREMPUAN DI SMP NEGERI 3 PUJUD T.P. 2013/2014 - Nurman Syahputra Nurman Syahputra; Raja Arlizon Raja Arlizon; Abu Asyari Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractIssues examined in this study consisted of eight aspects: 1. Aspects of circumstances and family relationships (KHK). 2. Economic and financial aspects (EDK). 3. The physical and health aspects (JDK). 4. Aspects of leisure time (WSG). 5. Aspects of education and learning (PDP). 6. Aspects of religious and moral values (ANM). 7. Aspects of the self (DPI). 8. Aspects of social relationships (HSD). The method used in this research is descriptive method: an organized method to address own problems concerning symptoms or phenomena occurring at the present time is to obtain a picture or circumstances that are applicable in the present and what it is. The data used is primary data is data that comes from first-hand about the problems experienced by male students and female students. The data were obtained using a check list of money problems The problem checklist of Roos and Leonard Mooney V Curtains published by Winkel and has been adapted by Prayitno be Uangkap Tool Problem (AUM). Questionnaires were distributed to 85 students are being sampled, samples were taken from all members of the population. Data already collected is presented in the form of data tabulation and then grouped according to their level. From the results of this study provide a general description that students of SMP Negeri 3 Pujud having problems with the following levels: a very prominent problem experienced by male students is Aspect Education and Lessons of 41.67%. While female students are the same aspects that aspects of Education and Lessons of 36.01%, the aspect of Social Relations at 11.08% while female students aspects of Social Relations at 15.41%, aspect and Relationships condition 10.39% on the aspect of self personal female students 12.98%, the male students aspects of personal 10.01%, 12.17% Family Relationship aspects, physical aspects of health and 10.39%, aspects of religion and moral values 9.43%, and students female aspects Religion and Moral Values of 7.26%, economic and Financial aspects of 4.39%, and female students of economic and financial aspects of 2.94%, then 3.27% aspects of leisure time for male students, and 2.82 % for female students on aspects Freetime. Keywords : student identification issues male and female